To evaluate and compare the primary stability of self-drilling orthodontic titanium mini-implants (Modern Orthodontics) inserted at various angles into polyurethane bone blocks using a pull-out test- An In-Vitro Study - Irfan Foujdar, . Abdulrehman; Rekhate, Chaitali Purushottam; Patil, Sameer; Potnis, Sheetal; Mhaske, Arun; Jethe, Sandeep (Journal of Neonatal Surgery, 2025)
Background: orthodontic mini implants are widely used nowadays in orthodontic practices. It is made up of various materials, due to its advantage of greater anchorage control and better patient compliance they play a pivotal role in orthodontic treatments. Primary stability of these mini implants at different angulations is tested in this study. Aim & Objective- The objective of this study is to assess and compare the primary stability of self-drilling orthodontic titanium mini-implants (Modern Orthodontics) inserted at various angles into polyurethane bone blocks using a pull-out test. Material & Methods- 24 new orthodontic titanium mini-implants having diameter and length of 1.6 x 8 mm were purchased and inserted in polyurethane foam bone blocks simulating cortical and cancellous bone layers having density of 50 PCF and 40 PCF respectively with help of implant driver manually. Each specimen underwent a pull-out strength test using the Universal Testing Machine at a loading speed of 1 mm/min. Results- The mean distribution of Pull out Strength for Modern orthodontics inserted in polyurethane bone block at 900 and 600 was 205.15 ± 5.39 and 241.87 ± 11.59 respectively. A high statistically significant difference was observed in pull out strength at 600 and 900 angle (P<0.001). Conclusion- The findings reveal that the pull-out strength at 60° exceeds that at 90°, emphasizing the critical role of the insertion angle in mini-implant stability.